2021
DOI: 10.1136/annrheumdis-2021-220756
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence on ‘SARS-CoV-2 vaccination in rituximab-treated patients: evidence for impaired humoral but inducible cellular immune response’

Abstract: The role of SARS-CoV-2-specific antibodies in COVID-19 is not well established: reports indicate an increased risk of severe COVID-19 infections in Rtx-treated patients, 7 whereas other data have suggested that B cells are dispensable for resolving such infections. 11 The here presented data indicate that polyfunctional antiviral T cell responses are raised after SARS-CoV-2 vaccination in this high-risk population suggesting protection in the absence of virus-specific antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 12 publications
1
12
0
1
Order By: Relevance
“…Protection through immunization is achieved by an orchestrated immune response between different cellular subsets of innate (APCs) and adaptive immunity, such as B and T cells. Anti-B cell therapies like anti-CD20 antibodies (rituximab, obinutuzumab and ocrelizumab) and BTK inhibitors are associated with poor humoral SARS-CoV-2 vaccination responses, in patients with AIIRD [17][18][19][20] , multiple sclerosis 26 and CLL 27 . Since B cell depletion enhances the risks for poor Covid-19 outcomes 3 , but also can reduce anti-SARS-CoV-2 vaccine responses, it is of utmost importance to delineate the level of B cell repopulation necessary to achieve anti-vaccine responses and get insights into the complex relationship between antigen-specific B and T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protection through immunization is achieved by an orchestrated immune response between different cellular subsets of innate (APCs) and adaptive immunity, such as B and T cells. Anti-B cell therapies like anti-CD20 antibodies (rituximab, obinutuzumab and ocrelizumab) and BTK inhibitors are associated with poor humoral SARS-CoV-2 vaccination responses, in patients with AIIRD [17][18][19][20] , multiple sclerosis 26 and CLL 27 . Since B cell depletion enhances the risks for poor Covid-19 outcomes 3 , but also can reduce anti-SARS-CoV-2 vaccine responses, it is of utmost importance to delineate the level of B cell repopulation necessary to achieve anti-vaccine responses and get insights into the complex relationship between antigen-specific B and T cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, in particular under B cell depleting therapy with RTX, hampered humoral and cellular responses following influenza, pneumococcal and hepatitis B vaccination have been reported [11][12][13][14][15][16] . Data available about SARS-CoV-2 vaccine response in rituximab treated AIIRD patients reveal substantially impaired humoral [17][18][19] but partly inducible cellular immune responses 20 . However, little is known about the complex mechanisms between T, B and plasma cells, as well as the level of B cell repopulation necessary for proper vaccine response among RTX patients.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, (even with mRNA vaccines) analogous to what has been observed with traditional vaccines, patients with AIAIDs may present a reduced vaccine-induced immune response because of the disease itself as well as immunosuppressive therapy, with CCS and anti-CD20 mAbs nearly always implicated in the immunosuppressive effect. However, for anti-CD20 mAbs, the marked reduction of the antibody response is associated with substantial maintenance of the adaptive cellular immunity, as originally observed with the influenza vaccine [13] and recently confirmed with anti-COVID-19 vaccines [110], even towards some variants of concern, such as B.1.1.7 and B.1.351 [111]. All the authorized COVID-19 vaccines can stimulate specific cellular immunity (Table 4) Moreover, immunosuppressive treatment has even been associated in some studies, with a protective effect on the cytokine release syndrome [112] observed in some cases of SARS-CoV-2 infection.…”
Section: Immunosuppressive/immunomodulating Therapy and Covid-19 Vaccinesmentioning
confidence: 66%
“…In this themed issue of the Annals of the Rheumatic Diseases, focused on COVID-19 and SARS-CoV-2 vaccination in rheumatology, a number of papers have been assembled, which advance our understanding in this area and should allow for optimising the approach to this pandemic in the near future. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] To date, our understanding of COVID-19 risk in rheumatology comes primarily from observational registry-based cohorts. A clear signal has emerged in that patients receiving B-cell depletion therapy or high-dose glucocorticoids at baseline are at higher risk of more severe COVID-19 outcomes if infected.…”
Section: Editorialmentioning
confidence: 99%